2020
DOI: 10.21203/rs.3.rs-70959/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Determinants of Health and COVID-19 Among Patients in New York City

Abstract: Background: Covid-19 testing and disease outcomes according to demographic and neighborhood characteristics must be understood.Methods: Using aggregate administrative data from a multi-site academic healthcare system in New York from March 1 – May 14, 2020, we examined patient demographic and neighborhood characteristics according to Covid-19 testing and disease outcomes.Results: Among the 23,918 patients, higher proportions of those over 65 years old, male sex, Hispanic ethnicity, Medicare, or Medicaid insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 3 publications
3
19
0
Order By: Relevance
“…However, Hispanic patients were underrepresented in the Optum population relative to the census population (Table 1). Our findings related to minority populations and sub-optimal health insurance are consistent with prior research demonstrating the importance of societal and economic inequities, differential exposure, access to tests over the course of the pandemic [12, 13, 16, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29].…”
Section: Discussionsupporting
confidence: 90%
“…However, Hispanic patients were underrepresented in the Optum population relative to the census population (Table 1). Our findings related to minority populations and sub-optimal health insurance are consistent with prior research demonstrating the importance of societal and economic inequities, differential exposure, access to tests over the course of the pandemic [12, 13, 16, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29].…”
Section: Discussionsupporting
confidence: 90%
“…Only 40 papers included the number of events for both hospitalised patients and outpatients. The 40 papers 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 underwent the quality assessment and were included in our meta‐analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review identified a total of 1,002,006 patients (188,597 hospitalised patients and 813,409 outpatients). The studies included 26 cohort studies, 26 , 27 , 28 , 29 , 30 , 32 , 34 , 35 , 36 , 37 , 42 , 44 , 45 , 46 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 60 , 62 , 63 , 64 7 cross‐sectional studies, 33 , 38 , 39 , 41 , 47 , 50 , 61 and 7 reports and case series 25 , 31 , 40 , 43 , 57 , 58 , 59 that were developed between December 2019 and December 2020. The included studies were conducted in the United States (27 studies), 25 , 26 , 28 , 30 , 31 , 32 , 33 , 35 , 36 , 38 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it has been found that communities with higher poverty, lower-income, and lower social security coverage have shown a higher prevalence of COVID-19. 29 Environmental factors such as living in a neighbourhood with poor air quality, insecurity related to housing, insecurity related to transportation, 30 household size, low educational level, [31] , [32] and public social security 33 have also been associated with a higher probability of having COVID-19 at the community level. These results are consistent with our findings, where a larger household size was also positively associated with a higher risk of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%